Luminescent, optical, magnetic and metamaterial behavior of cerium complexes - Iffat Ameen; Abhishek Kumar Tripathi; Raj Laxmi Mishra; Afshan Siddiqui; Umesh Nath Tripathi (Journal of Saudi Chemical Society)
The complexes of cerium with nitrogen, oxygen and sulfur donor ligands were prepared by conventional method. These newly synthesized complexes were characterized by FTIR, UV–Vis, DART Mass, TGA, PXRD, SEM and TEM techniques. The magnetic studies were carried out by the vibrating sample magnetometer. The optical constants were measured by absorption and reflection spectra as a function of wavelength. The concentration dependence of refractive index and absorption was observed by the experimental method, which reveals that these parameters are affected by change in concentration. The optical band gap obtained from Tauc-plot indicates its probability to be a good semiconductor. The luminescence behavior of these cerium complexes was observed by the absorption and emission spectra and the emission life time was calculated by their life time spectra. Keywords: Optical band gap, Refractive index, Magnetic studies, Luminescence